Safety and efficacy of super-high pressure OPN balloon in patients with in-stent restenosis - an intra-coronary imaging-based observational study - Kumaraguruparan, Lakshmi Durga; Polareddy, Dinesh Reddy; Kovvuri, Harilalith Reddy; Karthikeyan, Gautam; Malepati, Balakrishna; Vikash, V. M.; Shanmugasundaram, Sadhanandham; Sankaran, Ramesh; Senguttuvan, Nagendra Boopathy; Cuculi, Florim (Scientific reports, 2025)
Patients with in-stent restenosis have an increased risk of recurrence of major adverse cardiovascular events. Achievement of an adequate acute luminal gain is essential to minimize such recurrence. We compared the effect of utilization of Super-high pressure OPN balloon in patients with In-stent restenosis. This is an investigator-initiated single-centre observational study done at SRIHER, India. The primary outcome was procedural success, defined by intravascular ultrasound (IVUS). In addition, we intended to study the in-hospital clinical outcomes. We studied 30 patients, with 73.4% male and a median age of 66.5 years. Diabetes was present in 83%, hypertension in 60%, and chronic kidney disease in 20%. Left ventricular dysfunction (EF < 45%) was observed in 43.3%. In-stent restenosis (ISR) cases presented as chronic coronary syndrome (43.3%), NSTEMI (36.7%), and unstable angina (20%). Among 49 lesions, 48.97% were in the LAD, followed by the RCA (28.57%), LCx (20.4%), and LM (2.04%). OPN was used for pre-dilatation in 14 patients and post-dilatation in 13 patients while it was used for both pre- and post-dilatation in 3 patients. Regarding final treatment, drug-eluting stents (DES) was used in 21 cases (36 lesions), a covered stent in 1 case (2 lesions), drug-coated balloons (DCB) in 6 cases (9 lesions), and plain old balloon angioplasty (POBA) in 2 cases (2 lesions). Procedural success was obtained in all but one patients. ( n = 47 lesions) One patient had coronary perforation that was managed by a covered stent. At a median follow-up of 31 months (IQR-22), 4 (13.3%) patients had died; 1 due to potential stent thrombosis and 3 due to non-cardiovascular causes, and there was no MI or repeat revascularization. In our image-guided study, we found that OPN usage may be a safe and effective in patients with ISR lesions leading to a very good acute luminal gain.